An unusual association between pancreatic cancer and Purtscher-like retinopathy: Presentation of a unique case. (July 2022) - Intagliata, Eva; Giugno, Salvatore; Vizzini, Clarissa; Cacciola, Rossella Rosaria; Vecchio, Rosario; Vecchio, Veronica
Abstract: Introduction: Purtscher's retinopathy causes sudden loss of vision of varying severity, secondary to head injury or chest compression. Its pathophysiology is unclear. Purtscher's-like retinopathy has more attenuated clinical and objective features and can be associated with many non-neoplastic pathologies. Otherwise, an association of this kind of retinopathy with malignancies has been described once in the Literature. We present a case report on a unique association between pancreatic cancer and Purtscher-type retinopathy. Case presentation: A 79-year-old man with reduced central vision in both eyes required an ophthalmic evaluation. Visual acuity was 20/40 in the right eye and 20/50 in the left eye. Fundus examination showed yellow-white peripapillary spots and bilateral retinal hemorrhages in the superficial retina. The patient complained of abdominal pain and received a CT scan of the abdomen, which showed a pancreatic mass extending into the spleen. A percutaneous needle biopsy sample showed mucinous pancreatic adenocarcinoma. Clinical discussion: This case report should warn of a possible association between pancreatic adenocarcinoma and Purtscher's-like retinopathy. Conclusion: Patients with this kind of retinopathy should be evaluated to rule out not only benign associated disease, but also malignant tumors of the pancreas. Highlights: Patients with Purtscher-like retinopathy should be evaluated to rule out malignant tumors Association between pancreatic adenocarcinoma and Purtscher-like retinopathy has never been described in the Literature This case report should warn of a possible association between pancreatic adenocarcinoma and Purtscher's-like retinopathy